Visual prognosis in compressive optic neuropathy secondary to sphenoid sinus mucocele: A systematic review. (4th July 2018) - Li, Emily; Howard, Martha A; Vining, Eugenia M; Becker, Richard D; Silbert, Jonathan; Lesser, Robert L
ABSTRACT: Sphenoid sinus mucoceles (SSMs) are rare, benign lesions that can expand, often presenting with ocular symptoms—decreased vision, diplopia, visual field defects, proptosis, and external ophthalmoplegia. Reported cases are few, visual compromise varies, and factors affecting visual prognosis are poorly characterized. We investigate whether prompt surgical intervention (within 2 weeks of visual symptom onset) affects best-corrected visual acuity (BCVA) regained in patients with vision loss secondary to compressive SSM. We present a retrospective review of three cases and published literature to date. Our primary outcome was BCVA regained after surgical intervention; secondary outcomes included change in visual field defect and ophthalmological symptoms other than vision loss. Our three cases of SSM varied in onset, ranging from several hours to several months with patients aged from 13 to 80 years. All patients had severe vision loss to light perception (LP) or worse. Rapid neuro-imaging and urgent surgical intervention improved vision to count fingers at best. Of the two patients who underwent prompt decompression, one improved from no LP to LP and the other did not recover any vision. The patient who had visual loss for 3 months before intervention improved from LP to 20/400. Findings from our literature search, which yielded 12 cases of urgent intervention, supported the variability in visual prognosis despite prompt surgical intervention. SSMs are rare, pathologically benign lesions which can expand to cause ocular involvement. Prompt diagnosis and surgical decompression are recommended, but visual recovery may be limited even with urgent intervention.